2020
DOI: 10.21203/rs.3.rs-75521/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of the Marine Hatchery Built Environment on Mucosal Microbiome Colonization Across Ontogeny in Yellowtail Kingfish, Seriola Lalandi

Abstract: BackgroundMicrobial succession in vertebrates has primarily focused on vertical transmission and ontogenetic development in the mammalian gut. Teleosts comprise the majority of vertebrate diversity, yet little is known about how the microbiome develops in fish, particularly when vertical transmission is limited or absent for broadcast spawners. Biological factors such as diet, age, phylogeny, and trophic level along with environmental factors such as water salinity, temperature, and depth have been shown to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In contrast to the low microbial overlap between the intestine and water, we found a high microbial overlap between the intestine and feed. Microbial overlaps between the fish intestine and formulated feeds have been reported to be high [50,51] and low [52][53][54][55] in the literature. As discussed earlier, the feed microbiota detected by amplicon sequencing may have primarily originated from inactive microbes.…”
Section: Microbial Overlap Was Low Between the Intestine And Water Bu...mentioning
confidence: 99%
“…In contrast to the low microbial overlap between the intestine and water, we found a high microbial overlap between the intestine and feed. Microbial overlaps between the fish intestine and formulated feeds have been reported to be high [50,51] and low [52][53][54][55] in the literature. As discussed earlier, the feed microbiota detected by amplicon sequencing may have primarily originated from inactive microbes.…”
Section: Microbial Overlap Was Low Between the Intestine And Water Bu...mentioning
confidence: 99%
“…In line with previous studies in salmon (46)(47)(48) and other fish species (49-51), we found that microbial overlap between the intestine and water was low in the present study of salmon in freshwater. This may be explained by the fact that dur- (52)(53)(54)(55). As discussed earlier, the feed 346 microbiota detected by amplicon sequencing may have primarily originated from inactive microbes.…”
Section: Microbial Overlap Was Low Between the Intestine And Water But High Between The Intestine And Feedsmentioning
confidence: 94%